The preservation of cultural heritage in the newly formed small towns of northwestern São Paulo - Brunozi , Ana Helena; Cunha , Claudia dos Reis e (Technical and Scientific Journal Green Cities, 2024)
Despite the 1988 Federal Constitution enshrining a broad and democratic vision of cultural heritage, practices in the preservation field often persist with a narrow view of what should be considered cultural heritage. There remains a general and diffuse idea that heritage encompasses only monumental constructions, works by great artists, or creations from distant times. This conception, contrary to what the constitutional text proposes for the field of preservation, excludes a vast majority of Brazilian cities, particularly smaller and more recently established ones. This work aims to contribute to deconstructing the limiting idea of cultural heritage being restricted to only monumental assets and, consequently, to traditional preservation instruments. This will be achieved through a discussion on cultural heritage in small, recently established cities, focusing on the northwest of São Paulo state. Based on a literature review of authors such as Gatti and Zandonade (2017), Endlich and Detoni (2022), Campos and Inoue (2020), and Fontenele and Oksman (2018), the intention is to foster a critical and expanded understanding of the concept of cultural heritage. By discussing the relationship between heritage and small, recently established cities in the northwest of São Paulo, the aim is to reflect on how these cities can encompass local heritage, not only to protect it against imminent changes in the city and its spaces but also to preserve and reinterpret their urban identity over time and generations, thereby providing better quality of life, and fostering the appropriation and identification of the residents.
Keywords: Cultural Heritage; Small Towns; Northwestern São Paulo